Understanding Jesus healings: Shrinking history and Donald Capps"s different thinking cap - Aarde, Andries van (HTS teologiese studies, 2010)
This article is a critical appraisal of Donald Capps’s interpretation of the significance of Jesus’ healings for today. It focuses on Capps’s recently published book, Jesus the village psychiatrist. Capps sees Jesus as the ‘forerunner’ of the modern psychological profession. In his book he demonstrates that mental illnesses were known in antiquity. Referring to Sigmund Freud’s insights into the psychological phenomenon, hysteria, Capps interprets mental illness as ‘somatoform disorders’. According to Capps, Jesus’ deeds of healing should not be considered ‘miracles’ because this implies that they contradict natural laws. Building on the insights of historical Jesus research, Capps shows that these deeds of Jesus were performed ‘at the tension points between village and city, family and parents and children and between siblings’. Capps believes Jesus was a ‘psychiatrist’ because he ‘studied’, ‘treated’ and ‘prevented’ disorders of the mind. This article investigates the possibility whether Capps falls into the trap of ‘psychological fallacy’. The finding is that he does not; he deliberately avoids individualistic and ethnocentric anachronism. Nevertheless, the article criticises Capps’s indifference with regard to the socialscientific distinction between illness and disease, and curing and healing, respectively. Capps’s interpretation could be augmented by medical and anthropological insights and current studies on alternated states of consciousness.